A review to the specific problems of nano thermal physics. Issue 2 (December 2020) - Khvesyuk, V I; Barinov, A A; Liu, B; Qiao, W
Abstract: The paper is devoted to three current problems that related to thermal transfer in the solid-state nanostructures. The first task is the analysis of interaction of phonons with rough solid boundaries, the presence of which leads to a significant increase in the resistance to heat transfer in nanostructures. This fundamental problem is discussed in a connection to the theoretical formulation of rough interface between solids. The second task is exploring methods to calculate diffusion and heat transfer in solids within the framework of detailed consideration of phonon interaction processes. The development of the computational model that adequately represents the physics of interaction processes and allows to calculate thermal properties that are in a good agreement with experimental data remains open. The third task is to calculate the thermal bound-ary conductance. The problem is solved by considering the processes of scattering and refraction of elastic waves at the interface. For the first time, the dispersion properties of elastic waves are taken into account in the problems of this kind. The result is the applicability of the new model in a much wider temperature range than in the existing models.